2017
DOI: 10.1039/c6ra27480c
|View full text |Cite
|
Sign up to set email alerts
|

Brush-like block copolymer synthesized via RAFT polymerization for graphene oxide aqueous suspensions

Abstract: We report for the first time the applications of brush-like block copolymer in the dispersant of graphene oxide aqueous suspensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, as opposed to PDbS-rGO, PDrS-rGO was already aggregated at RT since the styrene part is difficult to anchor on the rGO surface because of steric hindrance by the long DMAEMA part (Figure S8, Supporting Information). [53] Therefore, architecture control is important for the dispersion of rGO. The obtained TEM, scanning electron microscopy (SEM), and Raman spectroscopy data demonstrated that graphene morphology was effectively controlled by a certain temperature due to the LCST properties of PDbS.…”
Section: Resultsmentioning
confidence: 99%
“…However, as opposed to PDbS-rGO, PDrS-rGO was already aggregated at RT since the styrene part is difficult to anchor on the rGO surface because of steric hindrance by the long DMAEMA part (Figure S8, Supporting Information). [53] Therefore, architecture control is important for the dispersion of rGO. The obtained TEM, scanning electron microscopy (SEM), and Raman spectroscopy data demonstrated that graphene morphology was effectively controlled by a certain temperature due to the LCST properties of PDbS.…”
Section: Resultsmentioning
confidence: 99%